Yield Evaluation and Selection of M6 Wheat Mutant adaptive to Medium Land - N. Nasaruddin; Muh. Farid Bdr; Yunus Musa; Hari Iswoyo (Universitas Sembilanbelas November Kolaka, 2019)
Wheat is a sub-tropical plant that can adapt well at altitudes of 1000 - 3000 m above sea level and requires relatively low temperatures. At this height, wheat crops in Indonesia are unable to compete with horticultural crops with higher economic value. This causes national wheat production to be very low and results in high wheat imports. Therefore, wheat varieties are needed that can grow and develop in Indonesia in the low to medium plains. The study aimed to test the adaptive mutant population descent in the middle plains to prepare multi-location tests and release of varieties. The benefit of this research is obtaining potential strains from high-temperature adaptive wheat mutants in the lowlands. This research was conducted using a randomized block design with three replications. The treatment consisted of 16 M6 Wheat mutants and four comparative varieties. The results showed that the genotypes of wheat mutants that had high production in M6 propagation in the central plains were N 350 3.7.1 (2.74 t. ha-1), N 350 3.6.2 (2.33 t.ha-1) and N 350 3.1.3 (2.26 t.ha-1). Characters that have high heritability values on M6 Number of stomata, chlorophyll index, plant height, number of tillers, productive tillers, rate of seed filling, panicle length, number of seedlings, empty percentage of florets, hollow seed weight, 1000 seed weight, and production